2022
DOI: 10.24996/ijs.2022.63.12.9
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR Gene Polymorphisms in Iraqi Kurdish Rheumatoid Arthritis Patients: Relation to Methotrexate Response and Toxicity

Abstract: Methotrexate (MTX) is still one of the gold standard treatments for rheumatoid arthritis (RA). It shows diverse outcomes in blood level and clinical response, this was demonstrated by its relation to the genetic polymorphism in the pharmacogenetic study. This study aimed to investigate the role of methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in relation to MTX efficacy and toxicity in Iraqi Kurdish RA patients. Sixty-four RA patients were involved in this study with an average age of 47.78 ±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This is the first study that examined the Arabic Iraqi population; however, recently, in another study that examined a different ethnic group (namely Kurdish) Iraqi RA patients, the authors concluded that genetic polymorphisms of MTHFR SNP (rs1801133 and rs1801131) are associated with MTX efficacy but not toxicity in RA patients 68 . The current study only found that rs1801131 was associated with treatment response, regarding the Kurdish-Iraqi study 68 , and in our study, no association between rs1801133 and rs1801131 with sex was found.…”
Section: Discussionmentioning
confidence: 92%
“…This is the first study that examined the Arabic Iraqi population; however, recently, in another study that examined a different ethnic group (namely Kurdish) Iraqi RA patients, the authors concluded that genetic polymorphisms of MTHFR SNP (rs1801133 and rs1801131) are associated with MTX efficacy but not toxicity in RA patients 68 . The current study only found that rs1801131 was associated with treatment response, regarding the Kurdish-Iraqi study 68 , and in our study, no association between rs1801133 and rs1801131 with sex was found.…”
Section: Discussionmentioning
confidence: 92%
“…[43][44][45][46][47][48][49][50] Pharmacogenomics studies concerning RA have emphasized the identification of genetic markers that may predict a patient's clinical response or the development of side effects for a given therapy, as well as assessing potential interactions between a patient's genetic profile and environmental factors. [51][52][53] This field holds promise for advancing personalized medicine and enhancing RA treatment approaches; this is the first research in the current literature that examined the association between several TYMS genes (657334C > A, rs2853741T > C, rs2606241A > C, and rs2853742T > C SNPs) with MTX treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…[43–50] Pharmacogenomics studies concerning RA have emphasized the identification of genetic markers that may predict a patient’s clinical response or the development of side effects for a given therapy, as well as assessing potential interactions between a patient’s genetic profile and environmental factors. [51–53]…”
Section: Discussionmentioning
confidence: 99%